Strategy to Increase Public Understanding in E-Toll Cards at the Tanjung Priok Access Toll Road (ATP) - Rofian Dedi Susanto; Diana Prihandini; Restu Ikhtiar (Sociometry Journal of Social Science, Art and Humanity, 2022)
Public Relations of PT. Hutama Karya (Persero) Tanjung Priok Access Branch (ATP) has disseminated information to the public regarding transactions at toll gates which are now non-cash. However, in reality, many people still do not care about the transfer or transition of transactions when entering the toll gate from cash to non-cash. There are still toll road users who lack balance when making transactions at the Toll Gate or do not carry an E-toll Card, so they cannot make payments when entering the Toll Gate. The purpose of this research is to study and analyze the PR strategy of PT. Hutama Karya (Persero) to increase public understanding of E-toll Cards on the Tanjung Priok Access (ATP) toll road to minimize the accumulation of vehicles due to lack of balance or drivers not carrying E-toll Card. This research is descriptive qualitative research with data collection techniques using interviews, observation, and documentation. Data analysis by the inductive way as well as text and media analysis. The results showed that the public relations strategy PT. Hutama Karya (Persero) Tanjung Priok Access Branch (ATP) is following Ruslan's Theory (2014), namely operational strategies, persuasive and educative approaches, public relations social responsibility approaches, cooperative approaches, and coordinative and integrative approaches. This is proven by the lack of obstacles in using the E-Toll Card on the Tanjung Priok Access (ATP) toll road and the solution to the problems faced.